Adaptive household strategies for sustaining crop production under conditions of water scarcity in semi-arid South Africa - Zhou, Leocadia; Mhlanti, Simphiwe; Slayi, Mhlangabezi; Muchaku, Shadreck; Dzvene, Admire R. (Frontiers in Sustainable Food Systems, 2025)
Water scarcity is emerging as one of the most pressing constraints to smallholder crop production in semi-arid regions, threatening the very basis of rural livelihoods that rely heavily on rainfed agriculture. In this context, small household gardens stand out as resilient spaces of food production, often more reliable and manageable than larger croplands exposed to climatic stress. This study explores how households in a semi-arid communal area of South Africa mobilize strategies to sustain crop production in gardens amid condition of persistent water scarcity. A mixed-methods approach was employed, incorporating a structured survey of 192 households and focus group discussions. Quantitative data were analyzed using chi-square tests, while qualitative data were thematically coded to capture local narratives. The results show that 63.1% of households are female-headed, with women more likely than men to experience crop failure due to water scarcity (53.3% vs. 27.2%). Education emerged as a significant factor (p < 0.05), with higher attainment associated with reduced vulnerability to water stress. While irrigation was widely practiced (78%), adoption of water-saving practices remained modest and skewed toward households with basic education and grant-based income. A clear distinction was observed between indigenous practices such as manuring and rainwater harvesting, commonly applied at the household level, and formal Climate-Smart Agriculture strategies, of which awareness and adoption remained low. The findings highlight compounded vulnerabilities among aging, female-led, low-income households and underscore the necessity for targeted, education-sensitive interventions to strengthen resilience in semi-arid food systems.